Caracterización de la distribución y concentración de la propiedad de la tierra y sus efectos en la productividad agrícola de las regiones del Valle del Cauca y Magdalena 2015 a 2019 - Forero Dorado, Elizabeth; Rangel Sobrino, July Paola; Ortiz Mojica, Jessica Marcela (Universidad Antonio Nariño, 2021)
This monograph-type research work aims to analyze the effects that the distribution and concentration of land ownership in Valle del Cauca and Magdalena have had on agricultural productivity during the period 2015 to 2019. The context of the analysis is carried out, taking into account that this situation is one of the most relevant problems that have been distinguished throughout history in the national territory.